Healing Through Words and Learning: Communication and Education Strategies in Drug Rehabilitation - Karaeng Azham Agus; Lindanur Sipatu; Rosida Adam; Arie Kurniawan (Nurul Jadid University, 2025)
This study aims to analyze the role of therapeutic communication and health education in enhancing the effectiveness of drug rehabilitation programs at the National Narcotics Agency (BNN) of Tojo Una-Una Regency. A qualitative approach with a case study design was employed through observation, in-depth interviews, and documentation involving ten informants—seven rehabilitation clients and three officers. Data were analyzed using Miles, Huberman, and Saldana’s Interactive Model with the support of Nvivo 12 Plus software. The findings reveal that therapeutic communication, encompassing openness, empathy, supportive behavior, positive attitude, and similarity, fosters warm and trusting interpersonal relationships between officers and clients. Empathy-based and family-oriented communication motivates clients to recover from addiction. Furthermore, health education guided by the Health Belief Model (HBM) improves clients’ risk awareness, self-efficacy, and understanding of the benefits of behavioral change toward a healthy lifestyle. Continuous and contextual education helps clients build resilience and reduce relapse risk. These findings emphasize that the success of rehabilitation at BNN Tojo Una-Una is not solely determined by medical interventions but strongly relies on the quality of interpersonal communication and sustainable health education as empowerment strategies for clients’ holistic recovery.